Avaliação de parâmetros de dosimetria para terapia fotodinâmica em bolsas periodontais - estudo clínico randomizado - Alvarenga, Letícia Heineck (2018)
Periodontitis is an inflammatory disease of the supporting tissues of teeth induced by microorganisms organized in biofilm and influenced by the immune response of the host. Mechanical periodontal treatment does not completely remove periodontal pathogens, and in specific cases, the use of systemic antimicrobials may be necessary. Aiming to reduce the use of antibiotics, antimicrobial photodynamic therapy (aPDT) appears as an alternative and can be used as adjuvant of periodontal treatment. However, the studies show discrepancies between the parameters adopted for PDT, and it is difficult to compare the results and measure their efficacy. The purpose of this study was to investigate parameters for photodynamic therapy in periodontal pockets. This clinical trial included 30 patients with chronic periodontitis and each patient had at least 3 incisors selected for the experimental procedures. The survival fraction of the microorganisms on the periodontal pocket; the dimer/monomer ratio of methylene blue on the pockets; and the pattern of light scattering in the gingival tissue were evaluated. It was used a laser with radiation emission at wavelength of ʎ = 660 nm and output radiant power of 100 mW and 3 irradiation times - 1, 3 and 5 min were adopted. The methylene blue (MB) photosensitizer (100 μM) was used in aqueous solution and associated with a surfactant (MBS). The results demonstrated the absence of antimicrobial effect with aqueous methylene blue mediated PDT. On the other hand, MB associated to the surfactant produced microbial reduction in the group irradiated for 5 min (p<0.05). The data obtained with the spectrometer showed that there were two absorption peaks in the MB in aqueous solution (relative to the dimer and the monomer), while in the MB associated to the surfactant, one absorption peak was observed correspondent with the monomer. The analysis of the photographs revealed that at 3 mm distance from the laser tip, there is 50% attenuation of the light intensity in all directions. In conclusion, the clinical use of PDT may be limited by factors that reduce the antimicrobial effect. Forms of irradiation and characteristics of the PS play important role on clinical aPDT.